Santripreneur in Santrendelik: Evidence of Pesantren Concern for Entrepreneurship and Religiosity - Hendri Hermawan Adinugraha; Mila Sartika; Muhammad Sulthoni (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This research examines the Santripreneur in Santrendelik in terms of tangible evidence of the pesantren’s concern for entrepreneurship and religiosity comprehensively. This qualitative research uses a phenomenological approach with triangulation as a source and analysis of the validity of the data. This study found that pesantren have an important role in developing the economic independence of Santri in the future. This research also proves that the concept of Islamic entrepreneurship also known as Santripreneur in Santrendelik is clear evidence of the pesantren’s concern for entrepreneurship and religiosity, this can be proven through two leading activities in Santrendelik, namely oxygen alms and goat bank. The oxygen alms program has become a concrete manifestation of Santrendelik’s concern for the environment and the future based on cooperation from various parties. Therefore, planting trees and protecting the environment so that it remains sustainable is a shared responsibility. Furthermore, the goat bank has become concrete evidence of Santripreneurs in Santrendelik, because the goat bank is a productivealms that can make alms funds optimally utilized for economic activities which in this case are goats so that the value of blessings and benefits is increasingly felt by the community.